FREQUENCY OF EPSTEIN-BARR VIRUS IN CLASSICAL HODGKIN LYMPHOMA - Azhar, Muhammad; Din, Hafeez ud; Muhammad, Iqbal; Hashmi, Shoaib Naiyar; Akhtar, Farhan (Journal of Ayub Medical College Abbottabad, 2016)
Background: Epstein-Barr virus plays an important role in pathogenesis of Hodgkin lymphoma. The first patient with Epstein-Barr positive Reed Sternberg cells was described in 1985. Since then association between Epstein-Barr virus and Hodgkin lymphoma has been shown in many parts of the world and its occurrence shows significant variation from continent to continent and from country to country. Method: The study was carried out at department of histopathology, Armed Forces Institute of Pathology from 27th April 2013 to 10th March 2014. A total of 55 cases of classical Hodgkin lymphoma were included in the study. Results: Out of 55 patients, 38 (69%) were male and 17 (31%) were female. The age of the patients ranged between 4-67 years with an average age of 29.4±21.72 years. Out of these, 44 cases (80%) were positive for latent membrane protein-1. Among positive cases 32 (72.72%) were male and 12 (27.28%) were female. Based upon histological subtypes MCHL was the commonest as a whole accounting for 87.3% as well as among both genders. Out of total 55 cases, 79.16% (38/48) of mixed cellularity Hodgkin lymphoma cases showed positivity for latent membrane protein-1 while 83.33% (5/6) cases of nodular sclerosis Hodgkin lymphoma and 100% (1/1) cases of lymphocyte depleted Hodgkin lymphoma showed positivity. No case of lymphocyte predominant classical Hodgkin lymphoma was diagnosed during the study. 80% of our classical Hodgkin lymphoma cases showed association with EBV expression. A total of 79.16% cases of mixed cellularity Hodgkin lymphoma showed LMP1 expression while 100% of lymphocyte depleted Hodgkin lymphoma showed LMP1 expression. Conclusion: The highest expression seen in lymphocyte depleted Hodgkin lymphoma subtype in contrast to mixed cellularity requires to be confirmed by a larger scale study comprising of substantial number of patients of lymphocyte depleted Hodgkin lymphoma and lymphocyte rich classical Hodgkin lymphoma. Keywords: Hodgkin lymphoma, EBV expression, LMP1.